The segment-to-frame association in word reading: early effects of the interaction between segmental and suprasegmental information - Sulpizio, Simone; Job, Remo (Frontiers in Psychology, 2015)
In four reading aloud experiments we investigated the operations occurring at the level of the phonological buffer by manipulating stress and phoneme information. In all experiments we adopted a masked priming paradigm with three-syllable Italian word targets. Experiments 1 and 2 tested the effect of pure segmental (e.g., fe%%%% – FEcola) and pure suprasegmental (CInema – FEcola) overlap, respectively. Experiments 3 and 4 tested the joint manipulation of segmental and suprasegmental information, by using prime-target pairs that shared the first syllable and did or did not share their stress pattern (e.g. FEgato – FEcola vs. feNIce – FEcola). The results showed that both segmental and suprasegmental primes affect reading at an abstract phonological level. Moreover, the joint manipulation of stress and phonemes showed an asymmetric pattern for different stress patterns, suggesting that the phonemic and the stress systems address the articulation planning through a process that starts as soon as the relevant information about the to-be-planned unit is active.